Kuota Perempuan di DPRD Jawa Tengah pada Pemilu 2014 dan Pemilu 2019 - Hamidah Abdurrachman; Ratna Riyanti; Rahmad Agung Nugraha (Perspektif Hukum, 2019)
Gender equality in Indonesian legislature has not yet reached its expected state. Despite numerous agreements, conventions, and affirmative actions that were taken so far to promote the agenda, the fact of the matter is that female politicians are still quite rare in Indonesian legislatures, compared to their male counterparts. Among some of the deciding factors that hinder women’s participation in politics, gender gap and transactional relationship in the election system are deemed to be the main ones. This article wants to address this problem by analysing the regulation of Indonesian general election and the way it affects female representation in regional Indonesian legislatures. Using a normative approach, this article will discuss secondary data through qualitative analysis. We have examined the number of female politicians in five regional House of Representatives in Central Java based on the election result of 2014 and 2019. Our findings showed that women's participation in those legislatures has not yet reached the 30% quota expected by the regulation. Based on this finding, we propose two necessary steps to attain the 30% quota goal. The need of a political warrant in practical level for female politicians beyond political party legitimacy and number-ordering of their candidacies.